MARKETING STRATEGY AND UTILIZATION OF MICRO MURABAHAH FINANCING PRODUCT IN COMMUNITY ECONOMIC EMPOWERMENT (Study at Bank BTPN Syariah Area Banda Aceh and Aceh Besar) - Munira, M.Ag (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2019)
This study aims to examine the mechanism of murabaha financing which was applied to banks Bank Syariah around Banda Aceh and Aceh Besar, knowing the application murabahah in products Package Future (PMD) on bank Bank Syariah around Banda Aceh and Aceh Besar towards economic empowerment and to examine the use of PMD micro financing products to the public welfare. The research method used in this thesis is descriptive research by collectingdata from literature research and field research. The data collection technique that writer use is a structured interview technique (guidance interview) by using questionnaire based on research that writer do to 2 areas of Banda Aceh and 2 areas of Aceh Besar with 32 customers are categorized 16 people as productive customers, 16 productive customers with increased financing and 9 officers bank BTPN Syariah. The results showed that all respondents recognize an increase in profits after financing from PMD products at Syariah bank. The increase in customer profits after taking PMD product financing ranges from 25% to 92%. Productive customers experience profit increases ranging from 50% to 75%, for productive and financing customers increased significantly increased business and profit increase ranging from 76% to 92% for delinquent customer category also experienced a 25% up to 67%. The result of the research shows that marketing strategy and mechanism of utilization of micro financing product at BTPN Syariah Bank succeeded in empowering people economy.